EKONOMI KELEMBAGAAN SISTEM USAHATANI PADI DI INDONESIA - RACHMAN, BENNY; -, SUPRIYATI; -, SUPENA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 2 Juli 2005)
This study was conducted in five regencies/rural which covered both java and outside java. This objective of this study are to get knowledge about the effect of policy government’s incentive and analyze Profitability Of rice farming. This results have important implications for Indonesia’s food policy, namely : (1) fertilizer market seem to be working well, as characterized by higher market competitiveness which increased efficiency, (2) in general, at five case districts gabah – rice market is quite well, as reflected by smaller marketing margin with a range 4 -6 % and restively competitive, (3) the performance at rice production cost showed that in both region have cooperative and competitive advantage to produce rice, for import substitutions. In order to improve the welfare at rice farmers the following factor should be taken into account, i.e. Input use balanced, reducing waste during harvest and postharvest, the improvement of gabah rendement, international improvement of input – output market, to enchance farmers accesibility to land, capital and technology, and diversified the source of household income, especially from off and non – agricultural activities.
Keywords: rural markets, fertilizer, rice, land, competitiveness